Exposing the limits in the residential building energy performance certification model - Vassiliades, Constantinos; Vardopoulos, Ioannis; Barone, Giovanni; Santamouris, Mattheos; Kalogirou, Soteris A. (My University, 2025)
This study examines the energy performance of residential buildings in Cyprus, focusing on the accuracy of the iSBEM-Cy Energy Performance Certification (EPC) system. Cyprus presents a unique context due to its Mediterranean climate and aging building stock, constructed mostly between 1980 and 2000 without energy efficiency regulations. This research investigates the discrepancies between simulated and actual energy consumption in typical Cypriot homes. Previous studies have highlighted the limitations of current EPC models, often showing significant variances between predicted and real-world energy usage. Using a comparative analysis, this study collects data from 15 residential units, examining heating, cooling, lighting, and hot water energy use. The results reveal notable differences, particularly in cooling loads, suggesting the need for improved modelling of user behaviour and local climate conditions. This research underscores the importance of accurate EPCs for effective policy-making and sustainable building practices, contributing to enhanced energy efficiency and reduced greenhouse gas emissions in the building sector. Future endeavours should prioritize integrating granular behavioural and climate-specific data to refine energy certification models further.
Keywords: Building Energy Efficiency; Energy Performance Certification (EPC); Residential Buildings; Simulation Accuracy; Sustainable Practices